Purification and Identification of an Antifungal Protein from an Isolated Fungus with Antagonism to Colletotrichum gloeosporioides MC9 - Yohana Avelia Sandy; Yo-Chia Chen; Liliek Sulistyowati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Colletotrichum gloeosporioides is the cause of anthracnose disease on mango. This disease becomes more damaging because it economically affects the harvested fruit during the postharvest season. In this research, eight isolates are isolated from the soil of a mango plantation. One of the isolates shows antifungal activity against C. gloeosporioides MC9. This isolate is identified as Penicillium citrinum isolate S1 based on the phylogenetic analysis of ribosomal rRNA sequence. From the culture of this isolate, extracellular filtrates are collected and evaluated for their antifungal activity. The mycelial growth of C. gloeosporioides is significantly inhibited by the culture supernatant of P. citrinum isolate S1. The culture filtrate is used to purify the antifungal protein using ammonium sulfate and ultrafiltration methods. Results show that the antifungal protein was estimated at around 40 kDa molecular weight when separated on a 10% Sodium dodecyl sulfate-polyacrylamide gel. After nine days of incubation, this antifungal protein’s inhibition effect with a concentration of 0.94 mg/ml remained 63.6% against C. gloeosporioides. The LCMS result showed that the antifungal protein belongs to the L-asparaginase superfamily. Based on this result, the antifungal protein produced by P. citrinum S1 has the potential to control mango anthracnose disease caused by C. gloeosporioides.